KEARIFAN LOKAL DAN PERAN ELIT AGAMA DALAM MERAWAT TOLERANSI ANTAR UMAT BERAGAMA DI AKAR RUMPUT - Ahmad Shobiri Muslim; Saiful Mujab (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
The aim of this paper is to find out the inter-religious dialogue among religions (Islam, Catholicism, and Hindu)in Kalibago sub-Village, Kalipang Village, Grogol District – Kediri Regency. By using participant observationand interviews with several leaders (sesepuh) from each religion. This article attempts to answer the questionon how the interreligious harmony in the research site is built and maintained. It found out that interreligiousharmony has been passed and maintained one generation to another generation where interreligious marriage,local wisdom, and the elders play a very significant role.